Cranial Morphology of Theriosuchus sympiestodon (Mesoeucrocodylia, Atoposauridae) and the Widespread Occurrence of Theriosuchus in the Late Cretaceous of Europe. (May 2014) - Martin, Jeremy E.; Rabi, Márton; Csiki-Sava, Zoltán; Vasile, Ştefan
Abstract : We present a detailed morphological description of the type-locality cranial material of Theriosuchus sympiestodon Martin, Rabi, and Csiki, 2010 from the Maastrichtian Densuş-Ciula Formation of the Haţeg Basin, Romania together with new material of isolated cranial elements and teeth from various sites of the same general area. The recognition of several individuals of distinct sizes allows for an assessment of ontogenetic variation in this taxon. New material, consisting of isolated teeth and an incomplete maxilla with in situ teeth, coming from various late Campanian/early Maastrichtian sites in southern France is referable to ? Theriosuchus sp. and hints to a rare but widespread distribution of Theriosuchus in the Late Cretaceous European archipelago.